Curriculum transformations in South Africa: some discomforting truths on interminable poverty and inequalities in schools and society - Ngobeni, Norah Risana; Chibambo, Mackenzie Ishmael; Divala, Joseph Jinja (Frontiers in Education, 2023)
In this paper, we argue that the different curriculum reforms South Africa embarked on have not really helped break the existing socio-economic inequalities. Precisely, the various reforms (e.g., C2005, NCS and CAPS) initiated by the South African government have been proved to be a flop and uninspiring considering that that schools have remained spaces where inequalities, violence, vandalism, harassment, stratification and various crimes continue to exist. Outside the schooling spaces, unemployment, poverty, xenophobia, robbery, GBVs, and different forms of crime have characterised South African society. Many educational researchers have also argued that these issues could symbolise a broken education system that is guided by shoddy policies. Accordingly, we sought to establish key issues that confront South African educational system in order to explain how these reproduce the apartheid-era-like inequalities. In the main, we established that neoliberal-minimalist policies have significantly influenced socioeconomic inequalities in South Africa. We also established that educational researchers have failed to identify neoliberalism as the root cause of South Africa’s inequalities. To achieve our goals, we utilised documents analysis to explain and understand how various policies, practices and powerful individuals have influenced these injustices. Theoretically, these debates have been guided by Paul Freire’s ‘Critical Pedagogy’ and Bourdieu ‘Social-cultural Capital mainly for their ability to illuminate power-relations, exclusions and inequalities through Symbolic Violence and depravations.